PANDANGAN HINDU MENYIKAPI PENYIMPANGAN PERILAKU REMAJA DITENGAH GEMPURAN SOSIALITA - Kadek Agus Wardana; I Wayan Titra Gunawijaya (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2023)
Teenagers are the foundation for the nation in continuing the norms of state and religion which cover all members of society. Religion is one of the many choices in guiding and changing the negative behavior of these teenagers. The concept of Hinduism itself has many rules/teachings to be able to introduce where the life of the teenager will take him. To produce valid and reliable data, this research uses qualitative research methods. To produce data that is logical, this study carried out several stages of data sorting in the form of: 1). Reducing data, 2). Display data, 3). Verifying data and, 4). Interpreting research data. Related references greatly support the validity of a scientific work, therefore library techniques are also used through a literature survey on Google Scholar. The deviant behavior of these adolescents is beyond the limits of reason in this global era, there are many cases that make parents sad to see developments and behavior that are beyond the limits of their age. Hindu teachings contain a lot of ethics to fix all the negative characters caused by people with deviant characters. Parents, educators, and government participation must be active in promoting what is conceptualized in the teachings of Hinduism so that they can anticipate unwanted events and the golden generation is saved from influences that tend to damage youth. Keywords: Hindu view, deviance, adolescent behavior, socialite